Child Friendly School Policy Analysis of the Principal's Role - Puspitasari, Renny; Wulandari, Ayu; Khamidi, Amrozi; Hazin, Mufarrihul; Purwoko, Budi (Universitas Muhammadiyah Gorontalo, 2025)
Child Friendly School (SRA) or also often called Child Friendly Education Unit is an educational policy that has the aim of creating an atmosphere and conditions of schools that are safe, inclusive, and support the growth and development of children. Principals have an important role in implementing the policy at the school level. This study aims to investigate the roles and challenges faced by school principals in implementing the Child Friendly School (SRA) policy. This research uses a review of relevant literature sources. The results stated that the role of school principals is very important in designing, implementing, and evaluating Child Friendly School (SRA) programs in schools. The principal has a role as a manager, supervisor, as well as a transformational leader who encourages synergy between school community members, then also ensures that child protection principles are applied, and ensures that all activities at school take place safely without violence, discrimination, and bullying. The challenges for school principals during the implementation of SRA include the limitations of adequate facilities and infrastructure, the lack of a comprehensive understanding of the concept of Child Friendly Schools, and the low involvement of parents in supporting the SRA policy in some schools. In conclusion, this study emphasizes the importance of strengthening the capacity of school principals through continuous training and formulating more practical policies so that the implementation of Child Friendly School (SRA) policies can run effectively and sustainably so that it can be optimally implemented in all schools in Indonesia.